2021
DOI: 10.3390/ijms222111519
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Anti-Glioblastoma Drug-Decorated Nanoparticle Delivery Systems Using Molecular Descriptors and Machine Learning

Abstract: The theoretical prediction of drug-decorated nanoparticles (DDNPs) has become a very important task in medical applications. For the current paper, Perturbation Theory Machine Learning (PTML) models were built to predict the probability of different pairs of drugs and nanoparticles creating DDNP complexes with anti-glioblastoma activity. PTML models use the perturbations of molecular descriptors of drugs and nanoparticles as inputs in experimental conditions. The raw dataset was obtained by mixing the nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Machine learning algorithms evaluating quantitative structure–property relationship (QSPR) emerged as a game-changer in this situation. The algorithms have been employed to design drug carriers, antibacterial nanoparticles, and other biomaterials. The algorithms can also unveil the complex relationship between the chemical structures of molecules constituting SAMs and their affinity to proteins. However, very few machine learning-based studies on various antibiofouling films have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning algorithms evaluating quantitative structure–property relationship (QSPR) emerged as a game-changer in this situation. The algorithms have been employed to design drug carriers, antibacterial nanoparticles, and other biomaterials. The algorithms can also unveil the complex relationship between the chemical structures of molecules constituting SAMs and their affinity to proteins. However, very few machine learning-based studies on various antibiofouling films have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This model could be applied for the screening of nanoparticle-drug complexes in glioblastoma. [31] The bagging ensemble method improves reproducibility of both cortical and subcortical functional parcellation of the human brain neuroimaging (more than 300 samples). [32] AdaBoost was used to differentiate colorectal neoplasia from normal tissue (AUROC up to 0.95 on 64 samples from 16 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Neurological conditions are among the most common medical system subject to ML model applications. [29,31,32,38,46,53,61-63,66,69,70] The most frequent type of data used in these applications were imaging data. Images consist of spatially coherent pixels in a local region, meaning that pixels close to each other share similar information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation